University Lifelong Learning in Europe and its Social Dimension. Conclusions from Practice - Waxenegger, Andrea (INSTED: Interdisciplinary Studies in Education & Society, 2017)
The article discusses the aspects of university lifelong learning (ULLL). It begins with the presentation of annual surveys conducted by the European University Continuing Education Network (EUCEN) among seventeen members of National Networks during years 2012?2015. Then, it discusses the actions of University in Graz showing in a practical way how a single high school can use ULLL in order to strengthen its ?social dimension? making it possible for target groups to obtain university education, which for various reasons have only limited access (or none) to scientific knowledge and academic education.